AN ANALYSIS OF EFL TEACHERS’ PEDAGOGIC COMPETENCE IN TEACHING ENGLISH AT SMP NEGERI 8 LUBUKLINGGAU - Wahyu, Annisa; Ramasari, Maria; Triyogo, Agus (Lingustic, Literature and English Education, 2023)
The aim of the research was to find out An Analysis of EFL Teachers’ Pedagogic Competence in teaching English at SMP Negeri 8 Lubuklinggau. However, the research was conducted at SMPN 8 Lubuklinggau and the time of this research was carried out on Augustus’ 2023. The researcher was chosen by using total sampling there were 2 English teachers in SMPN 8 Lubuklinggau. In this research, the researcher held on the observation in the first meeting in class, and last the researcher conducted an interview and given a questionnaire with two English teachers to know the teacher's pedagogical competence in teaching English at the seventh grade of SMPN 8 Lubuklinggau. However, the data was conducted by observation, interview and questionnaire. Based on the observation in general the teacher has done the criteria of pedagogical competence. Meanwhile, some steps were missing, in the data of the interview result and the questionnaire it also can be seen that English teacher A and B has good pedagogical competence.